Radical Landscapes: art, identity and activism - Pih, Darren (London : Tate enterprises, 2022)
Throughout the twentieth-century artists have responded to the landscape in emotional, physical and political ways: exploring themes of belonging to the land by interrogating the relationship between landscape history and identity, the enclosure or militarisation of land, to artists creating works that harness or dramatise natural earth processes. As the custodian of the national collection of British art, Tate's climate emergency declaration points to a wider concern and care for the environment that underpins the themes in Radical Landscapes. Structured on three broad thematic sections; 'Trespass', 'Landscape and Identity', and 'Climate Breakdown', there will be around 100 works in total starting from 1900 until today. Focussing on activism and how we value, care for, use and draw meaning from the natural landscape, the book will showcase an array of viewpoints reflecting the diverse perspectives in modern Britain, examining the artists' relationship to the landscape and social history as a stimulus for the imagination as much as action and protest. It presents a radical and outward-facing image of Britain and its diverse peoples and landscapes to the world. These conversations present a rare opportunity to reframe Tate's holdings of landscape art as well as explore how we might commune with nature and collectively work towards a more sustainable and equitable future. Artists include Henry Moore, Peter Kennard, Tacita Dean, Ingrid Pollard, Jeremy Deller, Rose English, Chris Killip, Derek Jarman, Yuri Patterson, Anthea Hamilton and many more.
Keywords: Landscapes in art; Artists; Artists Great Britain Exhibitions; Climatic changes in art; Great Britain; v; Nature (Aesthetics)